"Du bist einfach ein Schönling/ein Prachtkerl!" - zur Kontrastivität des expliziten Kompliments in der männlichen Kommunikation = "You are so handsome!" - on ambivalence and contrastivity of explicit compliments in men’s communication - Khrystenko, Oksana (Lebende Sprachen, 2022)
In this paper, the explicit compliments within male gender-homogeneous groups are examined in a contrastive way. There are some findings in gender linguistics that notice a low frequency of this speech act in male groups and ascribe certain thematic priorities to them. Although it has been postulated that compliments men exchange have more to do with the evaluation of their performance and authority assertion, [the] male complimenting behavior is also seen as highly ambivalent. The following study examines whether there are certain differences and similarities in the frequency, subject matter, grammatical and phonological design of explicit compliments in [the] groups of males with different cultural backgrounds.